2005
DOI: 10.1021/ja0520621
|View full text |Cite
|
Sign up to set email alerts
|

A Six-Bowl Carceplex That Entraps Seven Guest Molecules

Abstract: A six-bowl carceplex that entraps seven guest molecules, 5.(DMSO)7, was synthesized and characterized. The dynamics of the host shell was studied in solution in the absence and presence of water. A multiple-molecule template was found to drive the formation of 5.(DMSO)x.G(7-x) (G = DMA, DMF; x = 5-7). Higher selectivity was found for species containing greater numbers of DMSO molecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
31
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 44 publications
(49 reference statements)
0
31
0
Order By: Relevance
“…[5][6][7][8] The power of these supramolecular approaches is their ease and efficiency, best demonstrated in the quantitative synthesis of nanoscale capsules that are large enough to accommodate multiple guests. [9][10][11][12] Even though similar sized covalent container molecules, constructed from five or six cavitands, have been prepared in multiple steps, [13,14] an approach for their synthesis with efficiencies that are comparable to those of supramolecular approaches remains elusive. Herein, we report the nearly quantitative one-pot synthesis of a nanoscale container molecule by making use of dynamic covalent chemistry.…”
mentioning
confidence: 99%
“…[5][6][7][8] The power of these supramolecular approaches is their ease and efficiency, best demonstrated in the quantitative synthesis of nanoscale capsules that are large enough to accommodate multiple guests. [9][10][11][12] Even though similar sized covalent container molecules, constructed from five or six cavitands, have been prepared in multiple steps, [13,14] an approach for their synthesis with efficiencies that are comparable to those of supramolecular approaches remains elusive. Herein, we report the nearly quantitative one-pot synthesis of a nanoscale container molecule by making use of dynamic covalent chemistry.…”
mentioning
confidence: 99%
“…66·(DMSO) 7 . 64 It should be pointed out that this is a very large carceplex which is a covalent analogue of noncovalently bound pyrogallolarene hexamers. The NMR data and MM2 calculations indicate that 66·(DMSO) 7 has a slightly flattened, non symmetric structure; it reversibly complexes water molecules to give 66·(DMSO) 7 · (H 2 O) x ; x is not known.…”
Section: Methodsmentioning
confidence: 99%
“…It should be pointed out that for such a large container, and for guests of similar shape and polarity, this selectivity is very high. 64 In the second example the tetraformyl cavitand 67 was a starting material. It was observed that one-pot reactions of 67 with ethylene 1,2-diamine 68 lead to covalently bound capsules of a different shape, in dependence on the kind of solvent; in THF the tetramer 69, in CHCl 3 the hexamer 70 and in CH 2 Cl 2 the octamer 71 are formed 10,11 .Octamer 71 is a square antiprismatic capsule in which each cavitand occupies one of the eight corners 11 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…26). Our approach strongly surpasses earlier multistep covalent synthesis of related nanocontainers in its simplicity and efficiency, which should facilitate applications in medicinal, analytical, chemical and material sciences 27,28 . Important was the choice of imine bonds to connect building blocks during the synthesis.…”
Section: Introductionmentioning
confidence: 95%